METHOD OF REAL-TIME VIDEO STREAM SYNCHRONIZATION IN THE WORKING ENVIRONMENT OF AN APPLE ORCHARD (Computer systems and information technologies, 2023)
Monitoring and analyzing the state of harvest in an apple orchard is essential for efficient horticulture. Unmanned aerial vehicles (UAVs) have been increasingly used for this purpose due to their ability to capture high-resolution images and videos of the orchard from different perspectives. However, synchronizing the video streams from multiple UAVs in real-time presents a significant challenge. The traditional controller-worker architecture used for video stream synchronization is prone to latency issues, which can negatively impact the accuracy of the monitoring system. To address this issue, the authors propose a decentralized method using a consensus algorithm that allows the group of UAVs to synchronize their video streams in real time without relying on a centralized controller device. The proposed method also addresses the challenges of limited network connectivity and environmental factors, such as wind and sunlight. The automated system that utilizes the proposed method was tested in an actual apple orchard. The experimental results show that the proposed approach achieves real-time video stream synchronization with minimal latency and high accuracy. As such, the SSIM index varies from 0.79 to 0.92, with an average value of 0.87, and the PSNR index – varies from 22 to 39, which indicates the decent quality of the received information from combined images. Meanwhile, the effectiveness of the developed system with the proposed approach was proven, which is confirmed by a high average value of 82.69% of the reliability indicator of detecting and calculating the number of fruit fruits and a low average level of type I (14.67%) and II (18.33%) errors. Overall, the proposed method provides a more reliable and efficient approach to real-time video stream synchronization in an apple orchard, which can significantly improve the monitoring and management of apple orchards.
Keywords: real-time video stream; synchronization; image stitching; apple orchard; unmanned aerial vehicles; decentralized approach